Dysregulation of Cells Cycle and Apoptosis in Human Induced Pluripotent Stem Cells Chondrocytes Through p53 Pathway by HT-2 Toxin: An in vitro Study - Zhang, Yanan; Liu, Huan; Lin, Xialu; Zhang, Feng’e; Meng, Peilin; Tan, Sijia; Lammi, Mikko J.; Guo, Xiong (Frontiers in Genetics, 2021)
Kashin-Beck disease (KBD) mainly damages epiphyseal growth plate of adolescents and suspectible to both genes and gene-environmental risk factors. HT-2 toxin which is a primary metabolite of T-2 toxin was regarded as one of the environmental risk factors of KBD. We used successfully generated KBD-hiPSCs and Control-hiPSCs, which carry different genetic information. They have potential significance in exploring the effects of HT-2 toxin on hiPSC-Chondrocytes and interactive genes with HT-2 toxin for the purpose of providing a cellular disease model for KBD. In this study, we gave HT-2 toxin treatment to differentiating hiPSC-Chondrocytes in order to investigate the different responses of KBD-hiPSC-Chondrocytes and Control-hiPSC-Chondrocytes to HT-2 toxin. Morphology of HT-2 toxin-treated hiPSC-Chondrocytes investigated by transmission electron microscope clearly showed that ultrastructure of organelles was damaged and type II collagen expression in hiPSC-Chondrocytes was down-regulated by HT-2 treatment. Moreover, dysregulation of cell cycle was observed, and p53, p21 and CKD6 gene expressions were dysregulated in hiPSCs-chondrocytes after T-2 toxin treatment. Flow cytometry also demonstrated that there were significantly increased amounts of late apoptotic cells in KBD-hiPSC-Chondrocytes and mRNA expression level of Fas was up-regulated. In addition, KBD-hiPSC-Chondrocytes presented stronger responses to HT-2 toxin than Control-hiPSC-Chondrocytes. These findings confirmed that HT-2 is an environmental risk factor of KBD and p53 pathway was interacted with HT-2 toxin causing damaged ultrastructure of organelles, accelerating cell cycle in G1 phase, and increasing late apoptosis in KBD-hiPSC-chondrocytes.